(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
This paper examines the pivotal role of radiology in trauma care from the perspective of nurses, who play a crucial role in coordinating patient care and facilitating diagnostic imaging procedures in emergency settings. Key aspects such as coordination and communication, patient assessment and preparation, facilitation of imaging procedures, adherence to safety protocols, and interpretation and communication of results are explored.